Obstacles facing football players in the honor division - sahsahi, mahdi; Zemmouri, belkacem (sports creativity, 2025)
There are many difficulties that affect a player's football career, remaining obstacles to achieving better results. It is essential to identify these obstacles in order to overcome them. The aim of this study is to identify the most significant obstacles hindering players from practicing football in the Honor Division Championship of the Batna Provincial Football League. This study was conducted at the amateur sports club, Thniet El Abed (CASTEL). The results of the study revealed the following: The most significant obstacles facing players at the club level, in descending order, are as follows: Obstacles related to facilities and administrative aspects ranked first. Obstacles related to time constraints and training programs ranked second. Obstacles related to the player's personal characteristics and psychosocial aspects ranked third.